Outcome of Percutaneous Peritoneal Drainage in High Risk Perforated Peritonitis - Mukhtiar Ali, Sarmad Younis, Aqeel Ashraf, Fazal Hussain, Capt Ihsanullah Sial, Muhammad Attique Sadiq (Pakistan Journal of Medical & Health Sciences, 2022)
Study Design: Prospective study Place and Duration: The study is conducted at Surgical A ward Mardan Medical Complex, Mardan and Surgery department of Ahmed Hospital, Bagh Azad Kashmir during the period from June to November 2021. Methods: There were 85 patients of both genders with ages 22-80 years included. Patients were included into the study after obtaining written permission from all participants. All the patients had high perforation peritonitis treated with percutaneous peritoneal drainage with local anesthesia. Post-operative success rate, mortality and complications among all cases were recorded. SPSS 22.0 version was used to analyze complete data. Results: Among 85 cases, 54 (63.5%) were males and 31 (36.5%) patients were females with mean age 51.7±8.71 years. COPD was mostly found among 29 (34.1%) cases, followed by ischaemic heart disease in 20 (23.5%) cases, congestive heart failure in 14 (16.5%) cases, cerebrovascular stroke 12 (14.1%) and 10 (11.8%) patients had comorbidity of steroid use. After drainage, improvement observed in urine output and in blood pressure. Post-operative effectiveness was found among 70 (82.4%) cases and 15 (17.55) patients died. In Post-operative, we found that the surgical site infection (SSI) was the most common symptom followed by chest infection. Conclusion: According to our findings and experience, the use of percutaneous peritoneal drainage under local anaesthesia in patients who have been reported late or are critically ill improves their general condition and allows them to be better prepared to undergo further surgery, which could ultimately save their lives.